A Review for Gastro - Retentive Drug Delivery System - Patole, Rutuja; Chaware, Bharatee; Mohite, Vishal; Redasani, Vivekkumar (Asian Journal of Pharmaceutical Research and Development, 2023)
Inadequate pharmacokinetic properties may be connected with the widespread use of oral dose forms in disease treatment. Because of the formulation's rapid transit through the gastrointestinal tract (GIT), it can be challenging to achieve therapeutic levels of the medicine in specific situations when it is barely soluble; In addition, some medications must work locally due to a gastric disease, although they only last a short period in the stomach. Numerous studies have been done to identify formulations that can enhance all of these characteristics while extending stomach residence time. Many orally delivered medications advantageous for from the extended stomach retention time provided by gastroretentive controlled drug delivery systems.With a focus on current methods for extending stomach residence duration, the study's objective was to examine, gather, and present the preceding and contemporary literatures in a shorter format. The current review briefly discusses the need for GRDDS., Pharmaceutical importance’s of GRDDS, Physiology of stomach, Stomach functionalities, Approaches of GRDDS, factors controlling gastric retention, advantages , disadvantages, Method of preparation of Gastro-retentive Multiparticulate system, Polymeric material in gastroretentive formulations, Evaluation of Gastroretentive dosage form, comparsion between Conventional and Gastroretentive drug delivery system.